Theoretical calculation of the activity coefficients of dilute aqueous solutions taking into account factors of electrical nature - Kravchenko, M.; Bereznytska, Y.; Vasylenko, L.; Fedorenko, S. (My University, 2022)
The work is devoted to development of the diluted water solutions activity coefficient calculation methodology, using the equalization of the self-agreed systems continuum electrodynamics and allocating processes which are characteristic for the electric system. The dependence of calculated ion activity factors on concentration of diluted water solutions, which are divided into three groups, was obtained. It is justified that for single- and two-valent electrolytes of the first group the influence of the general mechanism of interaction between ions is characteristic, which is determined by the action of ion electric gravity and it`s features. The growth of activity in the area of large concentration values for electrolytes containing hydrogen ion and lithium ion is shown. It has been found that the activity values in the area of electrolytes large concentrations increase is connected with the manifestation of forces of pushing electrical origin in processes, which are accompanied by redistribution of charges. On the basis of equalization for the dielectric component properties of electrolytes water solutions are described. The dependence for calculation of electric field potential, field strength and charge density were obtained. Given the change of diluted water solution internal energy for "i" class ions and free energy is obtained the expression for chemical potential ions. The calculation of the diluted water solutions activity average coefficient is proposed taking into account the nature of electric factors.
Keywords: Department of Environmental Protection and Labor Protection Technologies; activity coefficient; electricity factors; diluted water solutions; electrolyte; concentration; electric field potential; charge density; chemical potential; ions